ANALISIS GAMBARAN KOLABORASI PETUGAS KESEHATAN DALAM PENURUNAN BERAT BADAN PASIEN STROKE ISKEMIK - Munir, Nur Wahyuni; Ahmad, Musfirah (Universitas Islam Negeri Alauddin Makassar, 2019)
Introduction. Stroke is a disorder of local or extensive brain function that occurs suddenly and quickly, can cause death without other causes except blood vessels. Obesity is known as one of the causes of hypertension and stroke. Body Mass Index (BMI) is a simple tool or way to monitor the nutritional status of adults, especially those related to underweight and overweight. The purpose of this study was to determine the analysis of the picture of collaboration between health workers in reducing the weight of patients with ischemic stroke in Makassar City General Hospital. Method. This research uses descriptive design. Samples were taken using purposive sampling with 10 stroke patients who had BMI > 25. Research methods with observation and interviews. The instrument uses an observation sheet containing demographic data, measurements of blood pressure, weight, and height. Results. Health worker collaboration in reducing stroke patients' weight is more towards health education to patients and families. Health education in the form of a recommended diet such as high fiber, low salt, adequate mineral water intake, and increase physical activity, if there are no contraindications to medical diagnosis by a doctor. Discussion. Weight loss requires a process and the changes are not immediately visible in a short time, depending on the length of day of hospital stay, so that consistency in diet and physical activity is needed when at home. Keywords: health worker, weight, stroke patients